Fundamental solutions for the long-short-wave interaction system - İnç, Mustafa; Hassan, Samia Zaki; Abdelrahman, Mahmoud; Alomair, Reem Abdalaziz; Chu, Yu-Ming (De Gruyter Poland Sp Z O O, 2020)
In this article, the system for the long-short-wave interaction (LS) system is considered. In order to construct some new traveling wave solutions, He's semi-inverse method is implemented. These solutions may be applicable for some physical environments, such as physics and fluid mechanics. These new solutions show that the proposed method is easy to apply and the proposed technique is a very powerful tool to solve many other nonlinear partial differential equations in applied science.
Keywords: He's semi inverse method; LS system; traveling wave solutions; exact solutions; MATLAB 18